Interference of Indonesian Language on Japanese Language in the Use of Aizuchi (ç›¸æ§Œ) by Japanese Language Students in Medan - Taulia; Gapur, Abdul (International Journal of Culture and Art Studies, 2023)
Language interference or disorder often occurs in individuals who have acquired proficiency in multiple languages, including Japanese language learners at the college level. This research aims to analyze the interference of the Indonesian language in the use of aizuchi (backchanneling) in Japanese by Japanese language students in Medan, Indonesia. The study employs a qualitative approach with a descriptive method. The data consists of transcriptions of conversations between students and lecturers that contain instances of aizuchi interference. Data collection is conducted through observation using techniques such as eavesdropping and note-taking. The collected data is analyzed through data condensation, data presentation, and conclusion drawing. The findings reveal that the interference of the Indonesian language in aizuchi in Japanese primarily occurs at the lexical level, specifically in the utilization of Indonesian words as aizuchi in Japanese conversations. An example of this interference is replacing the Japanese word "hai" with the Indonesian word "iya." The students' experiences influence the identified interference in learning foreign languages and cultural factors. This research contributes to a better understanding of the interference of the Indonesian language in the use of aizuchi in Japanese and provides insights for teaching the Japanese language at the tertiary level.